Synchrotron and SSC emission models for the hot-spots of powerful radio galaxies - Brunetti, G (2002)
We present some preliminary results from synchrotron and synchrotron-self-Compton (SSC) emission models for the hot-spots of powerful radio galaxies. In addition to well known radiative models already reported in the literature, we include the computation of the spectrum of the emitting electrons as a function of the distance from the hot-spot centre. The radial evolution of the spectrum takes into account possible particle reacceleration, synchrotron, SSC and adiabatic losses. We concentrate on the case of the northern hot-spot of the radio galaxy 3C 295 where radio, optical and X-ray data are available.